Beneficios de la psicoprofilaxis obstétrica durante el trabajo de parto en gestantes atendidas en el Hospital Regional Docente Materno Infantil “El Carmen”, enero – marzo 2019. - Perez Laura, July Adama; Urbina Huatarongo, Luz Ayda (Universidad Privada de Huancayo Franklin Roosevelt, 2019)
Este estudio fue realizado en el Hospital Regional Docente Materno Infantil “El Carmen”, consistió en desarrollar un instrumento que permitió medir y evaluar los beneficios maternos y perinatales de la Psicoprofilaxis Obstétrica durante el trabajo de parto en gestantes. El objetivo es Determinar los beneficios maternos y perinatales de la Psicoprofilaxis Obstétrica durante el trabajo de parto en gestantes atendidas en el Hospital Regional Docente Materno Infantil “El Carmen”, enero - marzo 2019, Por lo tanto, se aplicó el método científico no experimental, tipo de investigación cuantitativo, retrospectivo y el nivel de investigación es descriptivo. Como resultado de la presente investigación se obtuvo información relevante donde el resultado es que si tiene beneficios la Psicoprofilaxis en el trabajo de parto.

This study was carried out at the Maternal and Infant Regional Teaching Hospital "El Carmen", which consisted of developing an instrument that allowed measuring and evaluating the maternal and perinatal benefits of Obstetric Psychoprophylaxis during labor in pregnant women. The objective is to determine the maternal and perinatal benefits of Obstetric Psychoprophylaxis during labor in pregnant women treated at the Regional Maternal and Infant Teaching Hospital "El Carmen", January - March 2019, Therefore, the non-experimental scientific method was applied, Type of quantitative, retrospective research and the level of research is descriptive.

This study was carried out at the Maternal and Infant Regional Teaching Hospital "El Carmen", which consisted of developing an instrument that allowed measuring and evaluating the maternal and perinatal benefits of Obstetric Psychoprophylaxis during labor in pregnant women. The objective is to determine the maternal and perinatal benefits of Obstetric Psychoprophylaxis during labor in pregnant women treated at the Regional Maternal and Infant Teaching Hospital "El Carmen", January - March 2019, Therefore, the non-experimental scientific method was applied, Type of quantitative, retrospective research and the level of research is descriptive.
Benefits of obstetric psychoprophylaxis during labor work in managers attended in the Regional Hospital for child Maternal “El Carmen”, january – march 2019.
Keywords: Gestante; Embarazo; Psicoprofilaxis Obstétrica